Results of the surgical treatment of diffuse pigmented villonodular synovitis (diffuse-type tenosynovial giant-cell tumor) of the knee - Herasymenko, S. I.; Kostogryz, O. A.; Kostogryz, Yu. O.; Babko, A. M.; Mayko, V. M. (Zaporozhye Medical Journal, 2021)
The aim. To develop a treatment algorithm with the aim of improving the treatment results of diffuse pigmented villonodular synovitis of the knee. To study and analyze the results of surgical treatment of diffuse pigmented villonodular synovitis of the knee. Materials and methods. The study was based on the results of treatment of 48 patients with pathohistologically verified diagnosis of diffuse pigmented villonodular synovitis (tenosynovial giant cell tumor) of the knee undergoing treatment at the State Institution “Institute of Traumatology and Orthopedics of the National Academy of Medical Sciences of Ukraine” from 2010 to 2019. Results. The best functional results can be achieved in patients with diffuse pigmented villonodular synovitis of the knee in stage I of the disease. Using the method of mathematical statistics to evaluate the results obtained, we see that scores obtained through the Lysholm Scoring Scale were statistically significantly different in stages before a surgery (P = 0.000782), 3 months (P = 0.00005) and 6 months after the surgery (P = 0.04); but over time, these differences diminished and became actually insignificant 12 months after the surgery (P = 0.89). Conclusions. Applying our therapeutic algorithm for the treatment of patients with diffuse pigmented villonodular synovitis of the knee, the outcome of the Lysholm score was excellent in 22 % of patients, good – in 45 %, satisfactory – in 21 % and poor – in 12 % of patients.